ANALISIS PENGARUH RASIO KEUANGAN, ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) TERHADAP RETURN SAHAM INDUSTRI TELEKOMUNIKASI DI INDONESIA - S Sudarsono (Universitas Mercu Buana, 2017)
Communication technology is always progressing increasingly over the years, the size of the potential market for the telecommunications industry in Indonesia make trading securities, especially shares in the telecommunications industry sectors which listed on the Indonesian Stock Exchange, become one of the profitable business for investors. Before investing, an investor needs to do the analysis to avoid investment failure. Some ways of analysis that can be used is by measuring the performance of the company using the financial ratios method, EVA, MVA and than connected them to predict the likelihood of return of shares to be invest. This study uses the data of annual financial statements published by the Telecommunications sector firms in the period 2008 to 2013, with a total population of six companies and using purposive sampling technique. Analysis technique used in this study was a multiple linear regression. The results indicate that financial ratios such as Earnings Per Share (EPS), Return on Assets (ROA), Debt to Equity Ratio (DER) and Market Value Added (MVA) has a significant effect on stock returns telecommunications sector listed on the IDX. While the Financial Ratios Return on Equity (ROE) and Economic Value Added (EVA) has no significant effect